A Methylene Blue–assisted Technique for Harvesting Lymph Nodes After Radical Surgery for Gastric Cancer: A Prospective, Randomized, Controlled Study. (February 2015) - Aoyama, Toru; Fujikawa, Hirohito; Cho, Haruhiko; Ogata, Takashi; Shirai, Junya; Hayashi, Tsutomu; Rino, Yasushi; Masuda, Munetaka; Oba, Mari S.; Morita, Satoshi; Yoshikawa, Takaki
Abstract : Harvesting lymph nodes (LNs) after gastrectomy is essential for accurate staging. This trial evaluated the efficiency and quality of a conventional method and a methylene blue–assisted method in a randomized manner. The key eligibility criteria were as follows: (i) histologically proven adenocarcinoma of the stomach; (ii) clinical stage I-III; (iii) R0 resection planned by gastrectomy with D1+ or D2 lymphadenectomy. The primary endpoint was the ratio of the pathologic number of harvested LNs per time (minutes) as an efficacy measure. The secondary endpoint was the number of harvested LNs, as a quality measure. Between August 2012 and December 2012, 60 patients were assigned to undergo treatment using the conventional method (n=29) and the methylene blue dye method (n=31). The baseline demographics were mostly well balanced between the 2 groups. The number of harvested LNs (mean±SD) was 33.6±11.9 in the conventional arm and 43.4±13.9 in the methylene blue arm ( P =0.005). The ratio of the number of the harvested LNs per time was 1.12±0.46 LNs/min in the conventional arm and 1.49±0.59 LNs/min in the methylene blue arm ( P =0.010). In the subgroup analyses, the quality and efficacy were both superior for the methylene blue dye method compared with the conventional method. The methylene blue technique is recommended for harvesting LNs during gastric cancer surgery on the basis of both the quality and efficacy.